Methods of Developing Professional Competencies of Primary Education Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the necessary aspects of the effective use of modern technologies, methods and individual approaches aimed at increasing the knowledge of students are highlighted in the development of professional competences of future primary school teachers.